Unraveling Conflict: Implementation of a Criminal Case Resolution Model With a Restorative Justice Approach in Sukoharjo - Suciyani, Suciyani; Ariyani, Evi; Masrukhin, Masrukhin; Dona, Fery; Farkhan, Farkhan (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
Traditional law enforcement often focuses on punishing perpetrators without regard to restoring victims and damaged social relationships. Restorative Justice (RJ) has emerged as an alternative that emphasizes restoring victim harm, offender responsibility, and repairing social relationships. Sukoharjo Regency implemented RJ to resolve criminal cases more humanistically and efficiently. This study aims to analyze the implementation of RJ in handling criminal cases at Sukoharjo Police, evaluate its compliance with Standard Operating Procedures (SOPs), and assess public views on this approach. This research used a qualitative method type empirical juridical. Data were collected through in-depth interviews with police officers, victims, perpetrators, and community leaders, as well as analysis of official documents such as police reports and related regulations. The results showed that the implementation of RJ at Sukoharjo Regency was largely in accordance with the established SOPs. The mediation process is conducted transparently and involves all relevant parties. The community generally has a positive view of RJ, considering it a fairer and more efficient way to resolve criminal cases. However, there are several obstacles, such as limited trained human resources and a lack of public understanding of the RJ concept. RJ implementation at Sukoharjo District Police has successfully achieved the goals of recovery and restorative justice, although there is still room for improvement. Increased education and socialization to the community is needed, as well as additional training for police personnel to become more effective mediators. Sukoharjo Police are advised to increase RJ socialization programs, provide ongoing training for officers, and strengthen coordination with community leaders to support more optimal RJ implementation. Penegakan hukum tradisional seringkali berfokus pada penghukuman pelaku tanpa memperhatikan pemulihan korban dan hubungan sosial yang rusak. Restorative Justice (RJ) muncul sebagai alternatif yang menekankan pada pemulihan kerugian korban, tanggung jawab pelaku, dan perbaikan hubungan sosial. Di Kabupaten Sukoharjo sudah banyak pengimplementasian Restorative Justice untuk menyelesaikan perkara pidana secara lebih humanis dan efisien. Penelitian ini bertujuan untuk menganalisis implementasi RJ dalam penanganan perkara pidana di Sukoharjo, mengevaluasi kepatuhannya terhadap Standar Operasional Prosedur (SOP), serta menilai pandangan masyarakat terhadap pendekatan ini. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam dengan aparat kepolisian, korban, pelaku, dan tokoh masyarakat, serta analisis dokumen resmi seperti laporan kepolisian dan regulasi terkait. Hasil penelitian menunjukkan bahwa implementasi RJ di Sukoharjo sebagian besar sudah sesuai dengan SOP yang ditetapkan. Proses mediasi dilakukan dengan transparan dan melibatkan semua pihak terkait. Masyarakat secara umum memiliki pandangan positif terhadap RJ, menganggapnya sebagai cara yang lebih adil dan efisien dalam menyelesaikan perkara pidana. Namun, terdapat beberapa kendala, seperti keterbatasan sumber daya manusia terlatih dan kurangnya pemahaman masyarakat tentang konsep RJ. Implementasi RJ di Sukoharjo berhasil mencapai tujuan pemulihan dan keadilan restoratif, meskipun masih ada ruang untuk perbaikan. Diperlukan peningkatan edukasi dan sosialisasi kepada masyarakat, serta pelatihan tambahan bagi personel kepolisian untuk menjadi mediator yang lebih efektif.  Sukoharjo disarankan untuk meningkatkan program sosialisasi RJ, menyediakan pelatihan berkelanjutan bagi petugas, dan memperkuat koordinasi dengan tokoh masyarakat untuk mendukung pelaksanaan RJ yang lebih optimal.